2014
DOI: 10.1007/s10964-014-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Marginalization, Social Integration, and Adolescents’ Educational Success

Abstract: Links between schools' demographic composition and students' achievement have been a major policy interest for decades. Using a racially/ethnically diverse sample from the National Longitudinal Study of Adolescent Health (N = 6,302; 54% females; 53% White, 21% African American, 15% Latino, 8% Asian American, 2% other race/ethnicity), we examined the associations between demographic marginalization, students' later social integration (loneliness at school, school attachment), and educational performance and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 61 publications
1
48
1
Order By: Relevance
“…In fact, Gorski spends little time critically assessing the quality of research in the field or the areas in which such research is lacking. But that does not mean that he is not contributing to that area of research that is so key to developmental understandings of youth and their educations, both in terms of their academic challenges (see Benner and Wang 2014;Serbin et al 2013;Kiang et al 2013) as well as the challenges that they bring to school (Brenner et al 2013;Lee et al 2013). Gorski relies on recent studies to argue that the problems plaguing poor children take root long before the first day of elementary school.…”
mentioning
confidence: 99%
“…In fact, Gorski spends little time critically assessing the quality of research in the field or the areas in which such research is lacking. But that does not mean that he is not contributing to that area of research that is so key to developmental understandings of youth and their educations, both in terms of their academic challenges (see Benner and Wang 2014;Serbin et al 2013;Kiang et al 2013) as well as the challenges that they bring to school (Brenner et al 2013;Lee et al 2013). Gorski relies on recent studies to argue that the problems plaguing poor children take root long before the first day of elementary school.…”
mentioning
confidence: 99%
“…Many of the district's lowest performing schools are the lowest performing schools in the state and also have the highest concentrations of minority students and students living in poverty. Benner and Wang (2014) found that racial/ethnic marginalization in schools had a negative impact on student achievement which was compounded by other SES-related factors. The DI can be considered a multiple-component construct of SES that includes both resource-based (income and parent educational attainment) and sociopolitical factors (race).…”
Section: Conceptualizing Socioeconomic Statusmentioning
confidence: 99%
“…An alternative theoretical framework was considered, such that an increase in socioeconomic heterogeneity positively and significantly predicts an increase in achievement growth of low SES students (Benner & Wang, 2014;Blau et al, 2001;Goldsmith, 2011;Hall & Leeson, 2010). The null hypotheses express no relationship in typical or higher growth rates of low SES students across school socioeconomic contexts.…”
Section: Study Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who have attended ethnically diverse high schools tend to earn slightly higher grade point averages during their first year of college compared to students who attend ethnically homogenous high schools (Tam & Bassett, 2004). It has also been found that students who have been marginalized by their ethnic minority status and/or their socio-economic status are more likely to struggle academically than their nonmarginalized peers (Benner & Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%